2021
DOI: 10.1088/1755-1315/842/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Pondok community participation in sustainable solid waste management practices

Abstract: This study is focusing on Pondok community participation in a sustainable solid waste management programme. Besides that, the factors that influence Pondok community participation, such as knowledge and awareness, were explored. This study adopted a stratified sampling technique with 99 respondents from Pondok Pasir Tumboh, Kota Bharu, Kelantan were participating in this study. The data was processed SPSS software with descriptive and inferential analysis. This study revealed that Pondok community has excellen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…Nonetheless, there is a significant weak association between awareness and practices (r=0.153, n=278, p=0.012). However, the study by Barudin et al [22] concluded that, while most people are aware of the need of recycling, this awareness does not always convert into recycling practices which contradict to the finding of this study that showed there are relationship between the awareness and practices of recycling.…”
Section: Relationship Between Recycling Practice With Knowledge and A...contrasting
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, there is a significant weak association between awareness and practices (r=0.153, n=278, p=0.012). However, the study by Barudin et al [22] concluded that, while most people are aware of the need of recycling, this awareness does not always convert into recycling practices which contradict to the finding of this study that showed there are relationship between the awareness and practices of recycling.…”
Section: Relationship Between Recycling Practice With Knowledge and A...contrasting
confidence: 99%
“…Nonetheless, the null hypothesis for education of head household between knowledge and awareness are not significant as the null hypothesis being accepted. So, based on this result it showed knowledge and awareness do not have different between education oppose to other study that suggest education play crucial role in knowledge and awareness of respondents in recycling [22].…”
Section: Socio-demographic Factors Influence the Knowledge And Awarenessmentioning
confidence: 51%
See 1 more Smart Citation
“…Waste collection in Malaysia almost covers all communities in urban areas, but only about 66% of the populations in rural areas of Malaysia are covered [2,5]. Consequently, waste is dumped in rural areas on the streets and drains [6].…”
Section: Introductionmentioning
confidence: 99%